Dynamic models for health economic assessments of pertussis vaccines: what goes around comes around.... - Rozenbaum, M; De Cao, E; Westra, T; Postma, M (2012)
Despite childhood vaccination programs, pertussis remains endemic. To reduce the burden of pertussis, various extended pertussis vaccination strategies have been suggested. The aim of this article is to evaluate dynamic models used to assess the cost-effectiveness of vaccination. In total, 16 studies using a dynamic model were included, of which four also studied the cost-effectiveness of extended pertussis vaccination strategies. Generally, adolescent vaccination was found to be cost effective, but not highly effective in protecting infants too young to be vaccinated. The models also predicted that owing to age shifts, reduced pertussis disease in adolescents and young adults comes with an increase in later stages of life. This underpins the use of dynamic transmission models for interventions directed against pertussis. In future, dynamic transmission models for pertussis should be used widely to further enhance understanding of pertussis epidemiology and of extended pertussis vaccination programs that are currently considered in various countries.